2017
DOI: 10.1055/s-0043-119872
|View full text |Cite
|
Sign up to set email alerts
|

The Jellyfish Sign: A New Sonographic Cervical Marker to Predict Maternal Morbidity in Abnormally Invasive Placenta Previa

Abstract: To investigate the value of a new cervical sonographic sign, called the jellyfish sign (JS), for predicting the risk of maternal morbidity in cases of abnormally invasive placenta (AIP) previa totalis. Retrospective evaluation of transvaginal (TV) and transabdominal (TA) scans performed in all singleton pregnancies with placenta previa totalis. JS, i. e. the absence of the normal linear demarcation between the placenta previa and the cervix, was evaluated by TV scans. The presence/severity of AIP and outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
(25 reference statements)
1
5
0
Order By: Relevance
“…Previous studies reported that the cervical length before delivery showed association with massive PPH in pregnancies with PP [23]. A new sonographic jellyfish sign, the absence of the normal linear demarcation between the placenta previa and the cervix, was also reported to correlate with maternal complications [24]. For patients with PP, the cervix was also included in the segmentation, as illustrated in Fig.…”
Section: Image Segmentationmentioning
confidence: 95%
“…Previous studies reported that the cervical length before delivery showed association with massive PPH in pregnancies with PP [23]. A new sonographic jellyfish sign, the absence of the normal linear demarcation between the placenta previa and the cervix, was also reported to correlate with maternal complications [24]. For patients with PP, the cervix was also included in the segmentation, as illustrated in Fig.…”
Section: Image Segmentationmentioning
confidence: 95%
“…Transvaginal sonographic assessment of the cervix in women with placenta previa has been suggested recently by some authors. Bertucci et al 30 introduced a new sonographic sign for the prediction of maternal morbidity in women with abnormally invasive placenta previa, the so-called jellyfish sign, defined as the absence of the normal linear demarcation between the placenta previa and the cervix. Although based on a small number of cases, their pilot study yielded a high specificity for both PAS disorder (95%) and need for Cesarean hysterectomy (96.2%).…”
Section: Discussionmentioning
confidence: 99%
“…The sonography was Performed transabdominal by setting the probe vertically without pressure on the pubic symphysis with a full bladder. After locating the placenta (especially placenta previa) and its involvements, the most bulging volume behind the bladder(area, perimeter, and volume), the lacune(diameter, length, number, and surface of the largest lacunae obtained by multiplying the length by the width), the most considerable thickness of placenta on the cervix in patients with placenta previa, the most considerable thickness of the placenta behind the bladder, the Jelly sh sign (7), and sponge cervix (10) were evaluated. Also, transvaginal ultrasonography is considered the bulging of the Cervix in its canal and sponge cervix.…”
Section: Methodsmentioning
confidence: 99%
“…Continuously, various studies have been introducing novel markers in the diagnosis of PAS; for example, the presence of Jelly sh sign, de ned as the absence of a normal linear layer between the placenta and cervix is associated with the amount of bleeding, the need for red blood cell and plasma transfusion, hospitalization in ICU, duration hospitalization and increased rate of hysterectomy during cesarean section (7); also, the presence of intracervical lakes de ned as anechoic area and hypervascular tortuosity inside the cervix can increase the rate of percreta and cesarean hysterectomy accompanied by typical symptoms of PAS (8). As a requirement in standardizing ultrasound markers in diagnosing PAS, The Fetal Medicine Foundation (FMF) 2021 de ned some markers, including the number of placenta lacunae, absence of posterior placental hypoechoic area, thin posterior placental myometrium, hypervascularity of posterior bladder or placental, etc.…”
Section: Introductionmentioning
confidence: 99%